Low-cost lower extremity screening to predict shoulder distraction force in college softball pitchers - Ulman, S. M.; Nebel, A. R.; Bordelon, N. M.; Oliver, G. D. (The American Journal of Sports Medicine, 2025)
Background: During a windmill softball pitch, the throwing shoulder experiences forces greater than the pitcher`s body weight. Various kinematic, kinetic, and performance factors have been related to shoulder forces and torques in softball pitchers, and softball research has examined clinical screening measures such as range of motion, muscular strength, and/or neuromuscular control. However, no studies have explicitly identified low-cost, clinic-friendly screening measures predictive of shoulder distraction forces in softball pitchers.